Youth justice - European and international developments - Dünkel, Frieder (Pravnik, 2024)
Youth justice has evolved in various forms, spanning from a purely welfareoriented to a justice-oriented approach. Recently, elements of restorative justice and children’s rights have been implemented, partly due to human rights movements underpinning the standard setting of the UN (Children’s Rights Convention), the Council of Europe (ERJOSSM 2008), and the European Union (e.g., the Directive 2016/800). The past decades have also seen an increasing influence of punitive thinking, though the decline of juvenile crime rates, particularly violent crimes, has moderated this punitive turn. Some countries have successfully resisted “punitive infections” and maintained a moderate juvenile law focused on diversion and educative alternatives instead of punishment. Slovenia is one such country, widely resisting a punitive turn. The Slovenian moderate approach was evident during Yugoslavian times, especially when compared to its neighbours (e.g., Serbia). The influence of Professor Alenka Šelih in fostering a moderate penal climate cannot be underestimated. A new reform development in Europe and the US is the expansion of the scope of youth justice to include young adults up to 21 years or even beyond (the Netherlands: 23). This reform movement and practice is based on new neuroscience evidence on brain maturation, as well as developmental and sociological evidence concerning the transition from childhood to adulthood. Slovenia, like Germany, was one of the forerunners in considering the application of youth justice dispositions for young adults. Although it is challenging to compare different systems in terms of effects and efficiency, some good practices can be identified by referring to human rights standards as a benchmark.